Hadiths Narrated by Al-Mundhir bin Malik, Abu Nadara Al-Abdi in Maximus Sunan of Al-Shafai - Collection, Study and Graduation – - Salih , Qaqa (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to God, Lord of the Worlds, and blessings and peace be upon the guide of humanity, and upon his family and all of has companions all and after. This research was entitled Hadiths narrated by Al-Mundhir bin Malik, Abu Nadara Al-Abdi in Maximus Sunan of Al-Shafai - Collection, Study and graduation - to show the biography of Al-Mundhir bin Malik, Abu Nadara Al-Abdi and include his personal and scholarly life, the biography of the author of Maximus Sunan by Al-Shafai, may God have mercy on him. He explains his journey in seeking knowledge, his scientific implications what he composed during his scientific career, and a number of his sheikhs and students. The hadiths narrated by al-Mundhir bin Malik are mentioned in the traditions of al-Shafai, which are four hadiths. Translation I sstate the hadith, as a document and text and then I graduate it. Then I state the translation of the narrators, and judging the support of the hadith the translating of the narrators if the hadith is correct, good or weak, and showing strange words in the body of the hadith. The research was concluded with a set of results and recommendations.